Legal Satisfaction of Electronic Authentic Diction Made Notary in Facing Industrial Revolution 4.0 - Rafiqi Rafiqi; Marsella Marsella (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Notary has the authority to make an Authentic Deed based on article 1867 of the Civil Code. Proof of evidence in writing is done by authentic writing or writing under the hand. Along with advances in technology, each transaction using electronic information technology makes it easy for parties to make agreements through online. However in reality the Authentic Deed made by a Notary Public must be adjusted to Law Number 30 of 2004 amending the Law Number 2 of 2014 about the position of Notary Public. The formulation of the problem in this research is How Positive Law about the Certainty of Authentic Deed Law conducted by a Notary by using Electronics and how the obstacles to the agreement by using the Electronic Deed conducted by a Notary. The writing method in this paper uses notative juridical and the nature of the research is perspective. Research results in writing are the legal certainty of an authentic deed made by a notary that there is no positive law relating to an authentic deed done online and authentic deeds made online are that the parties must face directly, good faith and the validity of electronic signatures whose authenticity is uncertain. Recomendation  that policies on authentic deeds need to be made electronically.